Preeclampsia Screening with Mean Arterial Pressure (MAP): Skrining Preeklamsia dengan Metode Pengukuran Mean Arterial Pressure (MAP) - Susanti, Ayu Juwita; Yani, Erna Rahma; Yudianti, Ika (Universitas Muhammadiyah Sidoarjo, 2022)
The Health profile of East Java shows that the tree highest causes of maternal death in 2019 are preeclampsia/ eclampsia which is 31,15%, bleeding is 24,23% and other causes 23,1%. Program that have been carried out The Government in reducing MMR includes the Reduction in Maternal and Infant Mortality Rate (PENAKIB) program. In this program, risk factor for preeclampsia are assessed by taking a history and physical examination, namely Mean Arterial Pressure (MAP). The purpose of this study is to determine the efforts of screening preeclampsia using MAP measurement method. The method used is a literature review obtained from 3 databases, which are PubMed, DOAJ and Google Schoolar. Keyword used in the literature search is “Screening OR diagnosis OR Prediction OR Early detection AND Pre-eclampsia OR Preeclampsia AND Mean Arterial Pressure OR Arterial Pressure”. From 16 journal articles, researchers conducted research at 11-14 weeks of gestation, found 11 articles, while in 5 articles, researchers conducted pre-eclampsia screening at various gestational ages such as at gestational ages 14-27, 19-24, 27-37. , 37-39 weeks, sensitivity of 6 studies ranging from 51-70% and 4 studies ranging from 71-90% and a specificity of 87% which were categorized as good. Based o the research result, preeclampsia screening is effective in the first trimester.